MEMÓRIAS DISCURSIVAS, LÍNGUAS E IDENTIDADES SÓCIO-CULTURAIS - Serrani, Silvani (Organon, 2003)
In this article, I discuss language learning from a discursivepoint of view. Thus, I examine the notions of socio-cultural identity, subjectiveidentification and discursive formation. In the first part of the text,arguments against a homogeneous view of identity result from consideringidentification processes as components of the heterogeneity of subjectand language. In the second part of the article, I discuss the implicationsfor the language learning process of real interdependence of subject, languageand discourse. In order to clarify the comprehension of how andwhy words do not signify in themselves, I present an illustration of metaphoricaland metonimic processes in language acquisition. I also commentan implementation of the notion of discursive formation in a predidacticanalysis of three texts of editorial discourse in journals of science.To conclude, I insist on the importance of going beyond the linguisticsystem and the level of intention when considering the implicit dimensionin language. I also criticize normative standards and myths of omnipotencein educational projects concerning second languages.